“PEOPLE FIRST” PUBLIC-PRIVATE PARTNERSHIP AS AN INSTRUMENT FOR SUSTAINABLE EVELOPMENT OF RURAL AREAS - Shylepnytskyi, Pavlo; Zybareva, Oksana V.; Lopatynskyi, Yurii (Institutul de Economie Agrara, Bucharest, Romania, 2022)
At present, the issue of ensuring sustainable development has become a fundamental principle not only for the existence but also for the survival of the countries of the world community. This is due to: limited and uneven distribution of resources, as well as the exhaustion of some of these resources; environmental, food, social, political and other issues; uneven development of the world community and widening this gap; existence of military conflicts, etc. The Sustainable Development Goals have been adopted by the world community at the United Nations level to change the situation for the better. One of the tools of their practical implementation is the cooperation of the state and private business in the form of People First Public-Private Partnership (PFPPP). The paper analyses the peculiarities of the use of People First PPPs in achieving sustainable development goals. In particular, the concepts of sustainable development and the goals of sustainable development are described. Public-private partnership (PPP) as a tool for cooperation between the state and private business in the development of the state's infrastructure complex and a manifestation of the trends of the New Public Management is studied. The use of the mechanism of public-private partnership in implementing the Sustainable Development Goals, and tendencies in its development are substantiated. The advantages of public-private partnership as a mechanism for the development of public infrastructure and the provision of related services are analyzed. The People First PPPs as a tool for achieving the goals of sustainable development has been studied. In particular, an assessment of this model of public-private partnership is provided, and its principles, criteria and performance indicators are analyzed. The implementation of People First PPP was studied on the example of the public-private partnership project in Khulna, Bangladesh, including its effectiveness. The main challenges faced by the initiators of People First public-private partnership projects are analyzed. Conclusions are drawn on the use of People First Public-Private Partnership in the implementation of sustainable development goals.
Keywords: sustainable development goals, public-private partnership, “People First”, public infrastructure, rural areas